NATO AND SECURITY IN BOSNIA AND HERZEGOVINA IMPACT AND CHALLENGES (Security Dialogues, 2025)
The North Atlantic Treaty Organization (NATO), comprised of 32 member statesfrom North America and Europe, represents the largest military and political alliance oftoday. Membership in NATO is widely accepted as a guarantee of security, but it has beena subject of political conflict in Bosnia and Herzegovina for an extended period, as wellas in other countries in the region. Currently, all Western Balkan countries (Albania, NorthMacedonia, and Montenegro) except Bosnia and Herzegovina and the Republic of Serbia arefull members of NATO. Under the guise of military neutrality, the Republic of Serbia rejectsthe desire for full NATO membership, citing the NATO bombing of the then Federal Republicof Yugoslavia in 1999 as a key argument against joining. Bosnia and Herzegovina initially hadunanimous support for full NATO membership after the signing of the General FrameworkAgreement for Peace in Bosnia and Herzegovina, but over time, this support weakened andtransformed into open opposition from representatives of the Republika Srpska entity. Thelack of a pragmatic and thorough assessment of the interests of joining NATO, consideringregional and global developments, Russian influence on the Balkans and the fact that thereis a new reordering of the fragmented order in which military-political neutrality loses itsmeaning, further complicates the integration process in Bosnia and Herzegovina. Analyze ofthe impact of Bosnia and Herzegovina’s membership in NATO and its consequences are infocus of this paper.
Keywords: NATO, Security, Bosnia and Herzegovina